Study of Characteristics for Physical and Mechanical Properties of Medium Carbon Steel Normalizing and Shot Peening Treatment Product - Supriyanto, Agung; Priyambodo, Bambang Hari; Margono, Margono; Yaqin, Rizqi Ilmal (Suara Teknik : Jurnal Ilmiah, 2023)
Steel is one of the metals that is widely used in today's rapidly growing industrial world. The need for manufacturing machine components is increasing. Efforts to improve the mechanical properties of steel can use heat treatment and surface treatment. One of the surface treatments that is often used in the industrial world is shot peening. This study aims to determine the effect of normalising and shot peening treatments on S45C medium carbon steel. The effect of the treatment is indicated by changes in microstructure results and surface and transverse hardness testing of the treatment results. The result is a change in the microstructure and hardness value of S45C carbon steel from the effect of normalising and shot peening treatment. Shot peening treatment causes the grains to become finer from the surface to the subsurface depending on the distance from the surface to the surface depth. These changes cause the surface and sub surface of S45C carbon steel to experience an increase in mechanical properties. The highest hardness in normalising heat treatment and shot peening treatment at 20 minutes was 316.4 HV.